Modelo alométrico para estimar la altura total de las especies forestales del bosque de terraza baja, distrito del Napo, Loreto, 2023 - Ricopa Bardales, Jorge Smit (2024)
In order to find the best fitting allometric model to estimate the total height of tree species, an evaluation of the low terrace forest in the Napo district was carried out. According to the results, 180 trees, 17 plant families, 37 genera and 42 species were identified. A total of 0.004 trees/ha were recorded for Pseudobombax munguba and Aspidosperma desmanthum. The results of Spearman's Rho test show that the two variables (Total height and DBH) have a weakly positive association (0.159). With a correlation coefficient of r = 0.521 and a coefficient of determination of R2 = 0.272, the cubic allometric model provides a best (Regular) fit to the relationship between DBH and total height. This means that approximately 27.2% of the variability of mean total height in the data is related to diameter. The claim that the cubic allometric model is inadequate for estimating the total height of forest trees is refuted.